Hybrid Input Shaping and Non-collocated PID Control of a Gantry Crane System: Comparative Assessment - Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail; Mohd Syakirin, Ramli (2009)
This paper presents investigations into the development of hybrid control schemes for anti-swaying and input tracking control of a gantry crane system. A nonlinear overhead gantry crane system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. To study the effectiveness of the controllers, initially a collocated PD-type Fuzzy Logic control is developed for cart position control of gantry crane. This is then extended to incorporate a non-collocated PID and an input shaper control schemes for anti-swaying control of the system. The positive input shapers with the derivative effects are designed based on the properties of the system. Simulation results of the response of the gantry crane with the controllers are presented in time and frequency domains. The performances of the control schemes are examined in terms of level of input tracking capability, sway angle reduction and time response specifications in comparison to the PD-type Fuzzy Logic control. Finally, a comparative assessment of the control techniques is presented and discussed.